Ex situ conservation of aquatic plants of wetlands of the sabana de Bogotá - Lina Marcela Camelo-Mendoza; Myriam Liliana Martínez-Peña; Hernando Ovalle-Serrano; Vilma Isabel Jaimes (Biota Colombiana, 2016)
An alternative for conservation of floristic diversity of region is the ex situ conservation, which depends on various environmental factors such as physical and chemical water conditions, local climate and the selected propagation technique. The objective of this research was to assess propagation technique of best performance by species, and identify environmental factors that influence growth rates, and phenology of selected species. The relationship between growth of 25 species selected and abiotic factors were examined in a term of 23 months. We measured once a month the cover percentage, length, height and basal diameter. Also, we analyzed 12 physical and chemical variables of the water of lake, and daily weather variables. The variation of water levels was main limiting factor for conservation of species ex situ. The species Bidens laevis, Ludwigia hexapetala and Ludwigia peploides showed high rates of growth in contrast to the high mortality of Cotula coronopifolia and Hydrocotyle ranunculoides. The phenological stages of some species were associated with the local climate pattern. Results suggest that the successful establishment of aquatic plants is determined by physical and chemical quality of water, and selected technique. Each technique depends on hydraulic, which is affected by temporal and special variations.